Encrusted Double-J Stents: Risk Factors Analysis - Besut Daryanto (Journal of Global Pharma Technology, 2016)
Introduction Since its introduction by Finney and Hepperlen in 1978, the double-J (DJ) stent has become a common armament that every urologist uses every day. The use of the DJ stent cannot be separated from the morbidity or complications that might occur, including discomfort arising from the insertion of stents, forgotten to remove, urinary tract infections, biofilm formation, and even encrustation of the stent. This research aims to determine the correlation between the risk factors in the formation of encrustation in patients with urinary tract stones. Materials & Methods This is a cohort study using the chi-square analysis and odds ratio calculation. We evaluated urine metabolite, urine culture, time of removal of the DJ stent, and encrustation formation in the DJ stent. Sixty patients with urinary tract stone and 60 without urinary tract stone participated in this research. Results The presence of urine bacteria and neglected DJ stent in the stone group and abnormal urine levels of magnesium in the non-stone group had significant correlation with encrustation formation of the DJ stent (P < 0.05). Conclusions various factors lead to encrustation formation in the DJ stent, and patients with a history of stones have more risk factors for encrustation formation.Keywords DJ Stent, Bacteria, Urine Metabolite, Neglected, Encrustation.